Pengaruh Word of Mouth dan World Class University terhadap Pemilihan Perguruan Tinggi - Ni Putu Nurwita Pratami Wijaya; Ratih Hurriyati; Puspo Dewi Dirgantari (Coopetition : Jurnal Ilmiah Manajemen, 2023)
Higher education competition is currently highly competition in Indonesia. Both state universities and private universities are competing to get students. Various methods are used to attract prospective students, one of them is Telkom University. This study aims to see the influence of Word of Mouth and World Class University on student decision to select the university. With a total sample of 130 respondents who are new students at Telkom University year academic 2022/2023 and data analysis was carried out with PLS-SEM. The results of the study show that the World of Mouth influences the decision for student  to select the university , then world class university also influences the decision of student to select the university